Grímnismál : a critical edition - Mattioli, Vittorio (University of St Andrews, 2017)
The purpose of this thesis is an in-depth analysis of the Eddic poem Grímnismál found in the manuscript known as Codex Regius (GKS 2365 4to), located in Reykjavík, dated to c. 1270 and a fragment (AM 748 I 4to), located in Copenhagen, dated to c. 1300. While a great deal of work has been done on Grímnismál as part of the Elder Edda, there is yet no specific edition focusing on it alone. New studies on Germanic paganism and mythology show its shifting nature and the absence of specific tenets or uniform beliefs throughout the Germanic speaking world and in time. The relatively absent sources are similarly scattered. As such, the thesis suggests a new method of study, following a focused historical approach in which only Grímnismál is analysed in an attempt to understand the beliefs of the people that composed it. The nature of pagan belief itself prevents one from drawing more general conclusions on ‘Norse mythology’ as a whole. Part 1 is divided into two chapters and deals with my approach, the nature of Germanic belief, and the sources available as well as techniques of interpretation for them, all relevant to the production of the arguments made in the thesis. Part 2 deals with Grímnismál itself: Chapter 1 provides an analysis of the manuscripts, Chapter 2 contains my editing notes and Chapter 3 analyses the contents of the poem, Chapter 4 consists of my conclusions to this study, focusing on the cosmology and the dating of the poem. Part 3 contains the edition of Grímnismál and is followed by Part 4 which is the commentary to the poem. The thesis is followed by two appendices, one containing a facing transcription of the manuscripts and the other being a glossary to all words used in Grímnismál. Finally, this thesis includes a digital edition worked on xml. This is available in the following link: https://starescomp.github.io/grimnismal/#idm140518410334752